MODEL PEMBERDAYAAN PETANI UBIKAYU MELALUI POLA KLASTER SISTEM AGRIBISNIS TERINTEGRASI DI KABUPATEN SUKABUMI PROVINSI JAWA BARAT - Himmatul Miftah; Ahmad Syarbaini (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
The  research  was  aimed  at  developing  a  society  empowerment  model through  a  cluster  pattern.    Empowerment  was  able  to  increase  income  through  the optimization  of farming resources to produce processed cassava products  with high selling and added values. The model was developed by the integration of upstream and  downstream  agribusiness  subsystems  by  using  a  cluster  pattern  that  involved various  components  including  farmers/farmer  groups,  processes  in  agribusiness system, and institutional system in cassava agribusiness in Sukabumi Regency.